IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 2 TAHUN 2018 TENTANG STANDAR PELAYANAN MINIMAL DI RUMAH SAKIT UMUM DAERAH INDRASARI KABUPATEN INDRAGIRI HULU - Adela Aliana; Emilda Firdaus; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Government Regulation (PP) Number 2 of 2018 concerning MinimumService Standards as the legal basis for administering public services. One of theproblems in the Implementation of Minimum Service Standards is that theperformance of the local government in the health sector at Indrasari Hospital doesnot reach 100%. Indrasari Hospital is a hospital that provides health services, eachtype of service must reach 100%. But at this time the health services at IndrasariHospital have not been able to meet the satisfaction of service recipients.The purposes of writing this thesis are: first, implementation of GovernmentRegulation Number 2 of 2018 Article 6 paragraph 6 concerning Minimum ServiceStandards at Indrasari Hospital, Indragiri Hulu Regency, second, inhibiting andsupporting factors for implementing minimum service standards at IndrasariHospital, Indragiri Hulu Regency, third, the efforts made by the Government ofIndragiri Hulu Regency in improving the Minimum Service Standards at IndrasariHospital, Indragiri Hulu Regency.This type of research can be classified as empirical or sociological legalresearch. The research was conducted at Indrasari Hospital, Indragiri HuluRegency. The population and sample are the Head of the Indragiri Hulu DistrictHealth Office, the Director of the Indrasari Hospital, the Head of Commission IVof the Indragiri Hulu DPRD, the Head of the Legal Department of the IndragiriHulu Regency. Sources of data used, namely: primary data and secondary data.Data collection techniques in research with observation, interviews, and libraryresearch.The conclusions that can be obtained from the research results are first, theimplementation of government regulation number 2 of 2018 concerning minimumservice standards at the Indrasari Hospital. namely factors from the hospital thatdo not carry out service delivery according to service standards the applicableminimum, the factor of facilities and facilities,and the community factor that lackstrust in service providers who will carry out medical procedures, and third and thehospital has not optimized the service according to minimum service standards aswell as the addition of inadequate facilities and infrastructure.Keywords: Government Regulations-Minimum Service Standards-Hospitals